2014
DOI: 10.3382/ps.2014-04224
|View full text |Cite
|
Sign up to set email alerts
|

Growth, livability, feed consumption, and carcass composition of the Athens Canadian Random Bred 1955 meat-type chicken versus the 2012 high-yielding Cobb 500 broiler

Abstract: A flock of the Athens Canadian Random Bred (ACRB), a 1955 meat-type chicken control strain, was raised alongside a flock of 2012 Cobb 500 fast feathering high-yielding broilers to determine selection changes over the past 57 yr. All birds were reared under management practices appropriate for the Cobb 500. Birds were weighed weekly and processed at 6, 8, and 10 wk. Whole carcass, carcass parts, and organs were weighed. Modern broilers outweighed ACRB at every age, ranging from 3.7 to 4.7 times the size of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3
3
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 9 publications
1
22
0
Order By: Relevance
“…These regions were substantially smaller than most of those identified using the regression approach and therefore contain fewer genes. The genes found in low-diversity regions did, however, suggest enrichment for muscle cell development functions, consistent with the high muscle content of broiler chickens and the known changes in broiler carcass composition over the last 50+ years (Collins et al 2014). A number of the regions identified were located near regions showing evidence of selection in one or more previous studies of chickens (Rubin et al 2010;Elferink et al 2012;Zhang et al 2012a,b) (see Table 3 legend for further details on comparison of regions).…”
Section: Characterization Of Regions Showing Reduced Diversitysupporting
confidence: 74%
See 1 more Smart Citation
“…These regions were substantially smaller than most of those identified using the regression approach and therefore contain fewer genes. The genes found in low-diversity regions did, however, suggest enrichment for muscle cell development functions, consistent with the high muscle content of broiler chickens and the known changes in broiler carcass composition over the last 50+ years (Collins et al 2014). A number of the regions identified were located near regions showing evidence of selection in one or more previous studies of chickens (Rubin et al 2010;Elferink et al 2012;Zhang et al 2012a,b) (see Table 3 legend for further details on comparison of regions).…”
Section: Characterization Of Regions Showing Reduced Diversitysupporting
confidence: 74%
“…The genes found in low‐diversity regions did, however, suggest enrichment for muscle cell development functions, consistent with the high muscle content of broiler chickens and the known changes in broiler carcass composition over the last 50+ years (Collins et al . ).…”
Section: Discussionmentioning
confidence: 97%
“…Fatty acid composition in the breast muscle showed the most breed and age interaction effects (Table 4). The absolute embryonic breast muscle weight is heavier in COBB when compared to ACRB (data not shown), and at six weeks of age, the weight of breast muscle in COBB is twice of one of ACRB [5]. Hence, as the embryo develops, the COBB breed grows more muscle and deposit more saturated FA and n-6 FA in the muscle.…”
Section: Discussionmentioning
confidence: 86%
“…Other parameters such as egg composition, conductance values, and hatch performance were not different between COBB and ACRB [4]. In post-hatch development, other studies showed that COBB had larger breast and leg muscles and had significantly greater fat pad, when compared to ACRB, but had smaller heart and liver as a percentage of body weights [5]. The cross-breed of AA × Peterson showed higher expression of c-fos and c-mys in the liver from E14 to D28 (post-hatch) of age.…”
mentioning
confidence: 99%
“…The reasons for the significant associations between the g.420 C>A SNP and gizzard percentage weight and wing weight are unknown. Collins et al (2014) reported that the gizzard percentage of an old-breed broiler strain (Athens Canadian Random Bred) was higher than that of a modern broiler strain (Cobb 500) slaughtered at the same age. Therefore, the phenomenon observed in this study might simply reflect a negative correlation between live weight and gizzard percentage weight.…”
Section: Discussionmentioning
confidence: 98%